A Pilot Study on Forensic Imaging of Mechanical Injuries - Bin Wu; Yang Li; Yang Li; Bin Wu; Xiao-Fei Hu; Zhi-Yuan Xia; Wei Li; Guang-Long He; Jian-Jun Li (Journal of Forensic Science and Medicine)
Background: Postmortem imaging has played an important role in the field of forensic medicine. Objective: To preliminarily explore the application value of cadaver imaging in mechanical injury. Methods: Three cases of mechanical injury were collected, and the external examination, postmortem computed tomography (PMCT), postmortem computed tomography angiography (PMCTA), and autopsy examination were performed in proper order to compare and analyze the diagnostic ability of postmortem imaging in the exploration of fractures, organ ruptures, and bleeding sources. Conclusion: Postmortem imaging (PMCT and PMCTA) has important application value in the analysis of cause of death, inference of injury objects, wound reconstruction, and search for bleeding sources. The combination of postmortem imaging and traditional anatomy can significantly improve the quality of forensic examinations.